Tumour-elicited neutrophils engage mitochondrial metabolism to circumvent nutrient limitations and maintain immune suppression. Issue 1 (December 2018) - Rice, Christopher; Davies, Luke; Subleski, Jeff; Maio, Nunziata; Gonzalez-Cotto, Marieli; Andrews, Caroline; Patel, Nimit; Palmieri, Erika; Weiss, Jonathan; Lee, Jung-Min; Annunziata, Christina; Rouault, Tracey; et al.
Abstract Neutrophils are a vital component of immune protection, yet in cancer they may promote tumour progression, partly by generating reactive oxygen species (ROS) that disrupts lymphocyte functions. Metabolically, neutrophils are often discounted as purely glycolytic. Here we show that immature, c-Kit+ neutrophils subsets can engage in oxidative mitochondrial metabolism. With limited glucose supply, oxidative neutrophils use mitochondrial fatty acid oxidation to support NADPH oxidase-dependent ROS production. In 4T1 tumour-bearing mice, mitochondrial fitness is enhanced in splenic neutrophils and is driven by c-Kit signalling. Concordantly, tumour-elicited oxidative neutrophils are able to maintain ROS production and T cell suppression when glucose utilisation is restricted. Consistent with these findings, peripheral blood neutrophils from patients with cancer also display increased immaturity, mitochondrial content and oxidative phosphorylation. Together, our data suggest that the glucose-restricted tumour microenvironment induces metabolically adapted, oxidative neutrophils to maintain local immune suppression. Neutrophils normally fulfil their metabolic demands by glycolysis and have limited mitochondrial activity. Here the authors show that tumours promote neutrophils adapted to oxidative mitochondria metabolism that function in the glucose-restrained tumour microenvironment to promote tumour growth by maintaining local immune suppression.